Isolation and characterization of Ulva prolifera actin1 gene and function verification of the 5′ flanking region as a strong promoter. Issue 1 (1st January 2018) - Wu, Chunhui; Jiang, Peng; Guo, Yang; Liu, Jianguo; Zhao, Jin; Fu, Huihui
ABSTRACT: Ulva prolifera is a green macroalgae with an extremely high growth rate that can accumulate biomass with considerable protein content. To set up an available seaweed expression system, a prior step is to isolate endogenous and strong constitutive promoters. For this reason, the full-length genomic actin1 gene from U. prolifera ( Upactin1 ) was cloned and its 5′ flanking sequence was obtained by genome walking. The Upactin1 open reading frame consisted of 1134 nucleotides encoding 377 amino acid residues. Besides 4 exons and 3 introns in the coding region, an extra leader intron was identified in the 5′ untranslated region. According to quantitative GUS assays based on transient expression, the promoter activity of the Upactin1 5′ flanking region was found to be several times higher than that of the widely-used cauliflower mosaic virus 35S (CaMV35S) in all tested species of Ulva . In addition, precise deletion of the leader intron led to a significant decrease of promoter strength in U. prolifera, and almost entire loss of strength in U. linza and U. pertusa . To our knowledge, this is the first report to prove function of a leader intron in algae. The 5′ flanking region of Upactin1 was shown to be a much stronger promoter than the foreign CaMV35S, and its activity was highly dependent on the presence of the leader intron. We propose that the Upactin1 promoter could serve as an endogenous and strong constitutive element for genetic engineering of U. prolifera .